Beyond Boundaries—Genetic Implications of Urbanisation and Isolation in Eastern Grey Kangaroos (Macropus giganteus) - Elizabeth Brunton; Alexis Levengood; Aaron Brunton; Neil Clarke; Graeme Coulson; Claire Wimpenny; Gabriel Conroy (Urban Science, 2025)
Understanding how urbanisation and habitat fragmentation influence wildlife is critical for biodiversity conservation. Fragmentation and population isolation can reduce genetic diversity, yet few studies have assessed these genetic impacts in urbanised environments. Eastern grey kangaroos (Macropus giganteus), widespread across eastern Australia, often inhabit landscapes shaped by urbanisation. Using single nucleotide polymorphism (SNP) data from scat and tissue samples, we compared genetic characteristics of kangaroo populations in urban and non-urban areas across three regions. We assessed the influence of habitat isolation on genetic diversity and relatedness at 18 study sites. Overall, urban populations did not show significantly lower genetic diversity than those in less developed areas (p > 0.05; Urban mean HO = 0.196, Non-urban mean HO = 0.188). However, populations fully isolated by roads, buildings, and fences exhibited reduced genetic diversity and increased inbreeding. Additionally, significant genetic differences were observed among regions. These findings suggest that while urbanisation alone may not always reduce genetic diversity, complete physical isolation poses greater risks to population genetic health. This study highlights how urban landscape features can shape the genetics of large terrestrial mammals and underscores the need for spatially informed urban planning and management strategies that maintain or restore habitat connectivity.